1992
DOI: 10.1128/jvi.66.7.4161-4169.1992
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular processing of the paramyxovirus F protein: critical role of the predicted amphipathic alpha helix adjacent to the fusion domain

Abstract: At a nonpermissive temperature, the group D temperature-sensitive mutants of Newcastle disease virus strain Australia-Victoria (AV) are defective in plaque formation, in inducing infected cells to fuse, and in incorporating the cleaved fusion glycoprotein, FI +F2, into virus particles. In this study, the F protein of AV, expressed in chicken embryo cells, was able to complement these mutants in a plaque assay, identifying the F gene as the gene containing the group D temperature-sensitive lesions. The F genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Interestingly, two mutations previously reported in this region are in the g and c positions on the helix (Fig. 1C, boxed letters) and result in proteins that -97 kd are temperature sensitive in folding (27).…”
Section: L155mentioning
confidence: 76%
See 2 more Smart Citations
“…Interestingly, two mutations previously reported in this region are in the g and c positions on the helix (Fig. 1C, boxed letters) and result in proteins that -97 kd are temperature sensitive in folding (27).…”
Section: L155mentioning
confidence: 76%
“…2C, lane 6). with the sequence of the cytoplasmic tail of the fusion protein (27). Preliminary results with this antibody showed that, while reactivity of this antibody to wild-type protein on Western blots was low if the protein was boiled prior to electrophoresis (data not shown), proteins incubated at room temperature or heated to 50°C were readily detected.…”
Section: Iknaadvmentioning
confidence: 96%
See 1 more Smart Citation
“…To understand the mechanism of F protein-induced membrane fusion, it is important to understand the role of different domains of the F protein in mediating fusion. While it is known that the fusion peptide and adjacent heptad repeat regions have important roles in fusion Sergel-Germano et al, 1994;Wang et al, 1992), the role of the cytoplasmic tail of the F proteins is less clear. Studies with human immunodeficiency virus type 2 and simian immunodeficiency virus envelope glycoproteins (env) have shown that cytoplasmic tail truncation mutants significantly enhance syncytia formation and alter the conformation of the external domain of env (Mulligan et al, 1992;Ritter et al, 1993).…”
mentioning
confidence: 99%
“…The antibody used for immunoprecipitation of the fusion protein was anti-Ftail (27). This antibody is a polyclonal rabbit antibody raised against a synthetic peptide with the sequence of the cytoplasmic tail of the fusion protein as described by Wang et al (28) .01 M NaCl) containing 1% Triton X-100, 0.5% sodium deoxycholate, and 2 mg of iodoacetamide per ml as previously described (25)(26)(27). Nuclei were removed by centrifugation.…”
Section: Methodsmentioning
confidence: 99%